Making history in Iran : education, nationalism, and print culture - Vejdani, Farzin (Stanford University Press, 2014)
Iranian history was long told through a variety of stories and legend, tribal lore and genealogies, and tales of the prophets. But in the late nineteenth century, new institutions emerged to produce and circulate a coherent history that fundamentally reshaped these fragmented narratives and dynastic storylines. Farzin Vejdani investigates this transformation to show how cultural institutions and a growing public-sphere affected history-writing, and how in turn this writing defined Iranian nationalism. Interactions between the state and a cross-section of Iranian society-scholars, schoolteacher.